Tocilizumab for severe COVID‐19 pneumonia: Case series of 5 Australian patients. (13th August 2020) - West, Timothy A.; Malik, Sameer; Nalpantidis, Anastasios; Tran, Tuan; Cannon, Christine; Bhonagiri, Deepak; Chan, Kevin; Cheong, Elaine; Wan Sai Cheong, Jenny; Cheung, Winston; Choudhury, Faisal; Ernest, David; et al.
Abstract: Aim: To describe the first Australian cases of severe acute respiratory syndrome‐coronavirus 2 (SARS‐CoV2) disease (COVID‐19) pneumonia treated with the interleukin‐6 receptor antagonist tocilizumab. Methods: Retrospective, open‐label, real‐world, uncontrolled, single‐arm case series conducted in 2 tertiary hospitals in NSW, Australia and 1 tertiary hospital in Victoria, Australia. Five adult male patients aged between 46 and 74 years with type 1 respiratory failure due to COVID‐19 pneumonia requiring intensive care unit (ICU) admission and biochemical evidence of systemic hyperinflammation (C‐reactive protein greater than 100 mg/L; ferritin greater than 700 μg/L) were administered variable‐dose tocilizumab. Results: At between 13 and 26 days follow‐up, all patients are alive and have been discharged from ICU. Two patients have been discharged home. Two patients avoided endotracheal intubation. Oxygen therapy has been ceased in three patients. Four adverse events potentially associated with tocilizumab therapy occurred in three patients: ventilator‐associated pneumonia, bacteremia associated with central venous catheterization, myositis and hepatitis. All patients received broad‐spectrum antibiotics, 4 received corticosteroids and 2 received both lopinavir/ritonavir and hydroxychloroquine. The time from first tocilizumab administration to improvement in ventilation, defined as a 25% reduction in fraction of inspired oxygen required to maintain peripheral oxygen saturation greater than 92%, ranged from 7 hours to 4.6 days. Conclusions: Tocilizumab use was associated with favorable clinical outcome in our patients. We recommend tocilizumab be included in randomized controlled trials of treatment for patients with severe COVID‐19 pneumonia, and be considered for compassionate use in such patients pending the results of these trials.